Anti-cancer effect of Atractylodes macrocephala extract by double induction of apoptotic and autophagic cell death in head and neck cancer cells (Bangladesh Journal of Pharmacology, 2017)
The apoptosis resistance restricts the efficacy of traditional therapies of head and neck squamous cell carcinoma (HNSCC). To overcome this problem, Atractylodes macrocephala, a traditional Korean and Chinese herbal medicine, has been used in clinical practice. In the present study, the anticancer effect of A. macrocephala extract was investigated and its underlying mechanisms using head and neck cancer KB cell line. The extract-induced cytotoxicity was mediated by autophagic cell death as well as apoptosis in HNSCC cells though extrinsic apoptotic pathway and the Akt/mTOR autophagic pathway. This study suggests that A. macrocephala extracts can be a potential drug to overcome side effects and susceptibility for head and neck carcinoma by double induction of apoptosis and autophagy.Video Clip of Methodology: 6 min 27 sec  Full Screen    Alternate